PELATIHAN MANAJEMEN KEUANGAN PADA UMKM FAJAR KEMULAU CLUB SURABAYA - Prastiwi, Estik Hari; Istiono, Istiono; Riswan, M Sihab (Jurnal Indonesia Mengabdi, 2023)
The knowledge of business management including financial maangement is really needed by the owners of SMEs so they can make financial reports of their businesses. Many SMEs do not separate money for family and money for business. It affects the smooth running of business operations because there is no capital to buy raw materials needed. The training aims to provide knowledge to SMEs about business management, especially financial management, so that SMEs shave knowledge about how to make cash flow, profit and loss reports so that SMEs know the amount of profit generated by their business. The method used is giving lectures (explaining financial management material) and discussions with training participants. The results of this training are expected to increase SMEs' knowledge of business management including basic knowledge of financial management, marketing management and operational management. The results of this training are expected to increase SMEs' knowledge about their business financial plans so that they know cash flow and can make profit and loss reports. SMEs also expected can predict future business plans so that they can increase SMEs' business income and profits.